Uso da cistatina C e de enzimas urinárias para avaliação renal de gestante hipertensa com e sem pré-eclâmpsia e submetida à anestesia subaracnoidea para cesárea - Altamirano, Ivania Guillermina Rodríguez [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Preeclampsia is a multisystemic disease that affects, among other organs, placenta and kidney. Objective: Using multiple biomarkers, assess renal function and tubular integrity after cesarean section in mild preeclamptic patients undergoing subarachnoid anesthesia. Methods: This prospective cohort study examined renal function and tubular integrity of 72 pregnant patients with gestational or chronic hypertension, with and without mild preeclampsia, after cesarean section under subarachnoid anesthesia, having as markers of glomerular filtration rate (GFR) cystatin C and creatinine plasmatic, and of tubular integrity, alkaline phosphatase (AP), γ-glutamyl transpeptidase (γ-GT) and neutrophil gelatinase associated lipocalin (NGAL) urinary, before cesarean section (T1) and 48 h after (T2), distributed among groups: mild preeclampsia (P, case group), n = 27; chronic hypertension and mild preeclampsia superimposed (PH, case group), n = 16; hypertension (H, control group), n = 29. Results: The GFR by cystatin C increased between T1 and T2 for all groups while the GFR by creatinine was significantly decreased in all groups. The values of NGAL increased from T1 to T2 in all groups, and the FA and γ-GT enzymes decreased significantly in T2 of the groups P and H. Conclusions: For the postoperative period of cesarean section of pregnant patients with mild preeclampsia, cystatin C and NGAL were biomarkers not free of bias for the study of renal function. The GFR measured by creatinine showed a slight decrease, consistent with the stress of the perioperative period. There was a reduction of brush border enzymes in hypertensive pregnant patients and in those with pre-eclampsia

A pré-eclâmpsia é uma doença multissistêmica que afeta, entre outros órgãos, placenta e rim. Objetivo: Utilizando vários biomarcadores, avaliar a função renal e a integridade tubular após cesariana em gestantes pré-eclâmpticas leves submetidas à anestesia subaracnoidea. Métodos: Este estudo coorte prospectivo analisou a função renal e a integridade tubular de 72 gestantes com hipertensão gestacional ou crônica, com e sem pré-eclâmpsia leve, após cesariana sob anestesia subaracnoidea, tendo como marcadores do ritmo de filtração glomerular (RFG) a cistatina C e a creatinina plasmáticas, e da integridade tubular a fosfatase alcalina (FA), γ-glutamiltransferase (γ-GT) e lipocalina associada à gelatinase neutrofílica (NGAL) urinárias, antes da cesariana (T1) e 48h após (T2), distribuídas nos grupos: pré-eclâmpsia leve (P), n= 27; hipertensão arterial crônica e pré-eclâmpsia leve sobreposta (PH), n=16; hipertensão arterial (H, grupo controle), n=29. Resultados: O RFG pela cistatina C aumentou entre T1 e T2 de todos os grupos. O RFG pela creatinina diminuíu significativamente em todos os grupos. Os valores de NGAL aumentaram de T1 para T2 em todos os grupos, e os das enzimas FA e γ-GT diminuíram significativamente em T2 dos grupos P e H. Conclusões: Para o período pós-operatório de cesariana de gestante com pré-eclâmpsia leve, a cistatina C e o NGAL não se mostraram biomarcadores livres de viés para o estudo da função renal. O RFG medido pela creatinina mostrou leve diminuição, compatível com o estresse do período perioperatório. Houve diminuição das enzimas da borda em escova nas gestantes hipertensas e naquelas com pré-eclâmpsia
Use of cystatin C and urinary enzimes for evaluation of renal hypertensive pregnant patient with and without preeclampsia and underwent subarachnoid anesthesia for cesarean section
Keywords: Anesthesia in obstetrics; Pré-eclâmpsia; Mulheres grávidas; Hipertensão; Anestesia em obstetrícia; Cesariana; Marcadores bioquímicos